Procurement of Educational Facilities and Infrastructure in Islamic Education Institutions - Febriyanti Febriyanti; Icha Suryana; Pira Mariska; Tri Septya Rohma; Meita Mutiarani; Nurhaliza Junianti (Sustainable, 2023)
This research aims to determine the meaning, principles, and objectives of providing facilities and infrastructure in education. This research uses qualitative methods with a library-based approach. The research results cover the meaning, principles, and objectives of providing facilities and infrastructure in education. Procurement of facilities and infrastructure in education is very important for achieving learning activities according to an education curriculum. Based on the discussion description, several conclusions were obtained: 1) Understanding the provision of facilities and infrastructure, namely the implementation of objectives, suitability between learning media and teaching materials, availability of adequate facilities and infrastructure, and the character of students. 2) the principles of facilities and infrastructure, namely a) the principle of achieving goals, b) the principle of efficiency, c) the principle of administration, d) the principle of clarity of responsibility, and e) the principle of cohesiveness. 3) the aim of providing facilities and infrastructure to support the learning process in achieving educational goals.